Hubungan Peran Keluarga Terhadap Kualitas Hidup Lansia: Literature Review - Kiasati Nur Amajida; Sheilla Maurie Arthamevia; Dini Nur Alpiah (CV. ALIM'SPUBLISHING, 2024)
The family has an important role in maintaining and improving the quality of life of the elderly. They can change the behavior of the elderly towards clean and healthy living habits, improve the environment, and provide health services. Good quality health can slow down the physical decline of the elderly. The important role of the family in maintaining the quality of life of the elderly includes creating good relationships, providing a feeling of security and comfort, listening to and meeting the needs of the elderly, as well as motivating and involving them in decision making. Family support also plays an important role in increasing the self-confidence of the elderly. Families can involve the elderly in making decisions and solving problems together, providing freedom in physical and mental changes, as well as providing space and time. This research aims to determine the relationship between the role of the family and the quality of life of the elderly. This research method is a literature review carried out using the PICO search on the Google Scholar database. There were 5 journals that met the criteria. Thus, it is important for families to provide support in maintaining the quality of life of the elderly.